Design and Development of Android Based Teeth and Mouth Disease Detection Expert System Using Dempster-Shafer Method - Kristian Kristian; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2016)
Teeth and mouth disease is a disease that affects many people in Indonesia. Teeth and mouth disease can interfere with human activities a link between oral health to overall body health including diabetes, heart disease, pregnancy problems, and memory loss. The quick detection of teeth and mouth disease would help people to quickly recover from teeth and mouth disease. This research was conducted with the aim to help detect teeth and mouth disease suffered by the user. In this research, the determination of the results of teeth and mouth disease detection was conducted using Dempster-Shafer method. This method is used because this method combines belief values of that the data is taken from the entire value of the trust that is available. This application was developed for android devices. This application was tested using ten kinds of cases designed by a doctor. Based on test cases conducted as many as ten kinds of cases, the results given by this application correspond 100% with the results that have been validated by drg. Lanny Widjaja. Index Terms: Android, Dempster-Shafer, expert system, teeth and mouth disease